KAJIAN IDENTIFIKASI PERATURAN PELAKSANA DALAM UU SISTEM NASIONAL ILMU PENGETAHUAN DAN TEKNOLOGI NO 11 TAHUN 2019 - Supadmi, Sri (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
Identification has been carried out regarding the implementing regulations of the National System of Science and Technology Law No 11 of 2019 (UU Sisnas Iptek). Science and technology become an important tool in the development of the state. Indonesia also realized the importance of science and technology by starting with the support of legislation in 2002 in the form of the National System Law on Research, Development and Application of Science and Technology No 18 of 2002. The law was later updated with Law No 11 of 2019.Identification is carried out against the articles in Sisnas Iptek Law No 11 of 2019 which states regarding implementing regulations. The result then becomes a reference for identification of appropriate regulations and is still valid today. From the results of the comparison and tabulation, it was obtained that Sisnas Iptek Law No 11 of 2019 requires 24 implementing regulations consisting of 21 government regulations and 3 presidential regulations. Of the 24 implementing regulations, there are already 6 appropriate regulations that are currently still in force, consisting of 5 government regulations and 1 presidential regulation.